Penetapan Harga Produk Industri Kerajinan Kayu UD. Akar Dewa Jati di Desa Karanganyar Kecamatan Kendit Kabupaten Situbondo dalam perspektif Etika Bisnis Islam - Misbahul Ali; Muhammad Imron (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
Odd pricing applied by UD. Akar Dewa Jati are only partly in wooden craft products. With the reason of attracting consumer interest and it is felt to be quite effective. The aim is to gain profits, gain market share and maintain the survival of industrial or business premises. Determining an odd price strategy is in accordance with Islamic business ethics by always prioritizing the principle of balance or fairness and responsibility in the form of honesty in conveying product prices, carrying out fair transactions and not committing fraud that could cause harm to other people. Meanwhile, for the remaining change from price rounding, if there is no change, it will be replaced with candy or transferred to social funds.